Gender and experiences of retaliation - Kely César Martins de Paiva; Hélio Arthur Reis Irigaray; Mariana Branquinho Macedo; Jesuína Maria Pereira Ferreira; Gizelle Souza Mageste; Michelle Regina Santana Dutra (Tourism & Management Studies)
Given the idiosyncrasies of call center work, its impact on the lives of employees and their possible reactions, we analyzed what forms of retaliation can occur in such an environment by considering gender. We performed qualitative descriptive research. We have interviewed 20 call center agents (9 men and 11 women) in Belo Horizonte, the capital city of Minas Gerais state, in Brazil. We fully transcribed all interviews and subjected the data to discourse analysis (the French approach). The results showed that in this case, there was no gender difference regarding perceived unfairness. Thus, workers of both genders often retaliate and consider their actions to be reasonable.